Allelic variants for Waxy genes in common wheat lines bred at the Lukyanenko National Grain Center - E. R. Davoyan; L. A. Bespalova; R. O. Davoyan; E. V. Agaeva; G. I. Bukreeva; Yu. S. Zubanova; D. S. Mikov; D. M. Boldakov (Вавиловский журнал генетики и селекции)
This article presents the results of a molecular marker-assisted study of allelic variants of Wx genes in common wheat (Triticum aestivum L.) lines. The study was carried out as part of the work on the transfer of null alleles of the genes Wx-A1, Wx-B1, and Wx-D1 to the varieties of soft wheat and creation of breeding material with modified activities of the main enzymes involved in amylose biosynthesis. The lines were obtained at the Department of Breeding and Seed Production of Wheat and Triticale, National Center of Grain named after P.P. Lukyanenko, by crossing mutant forms carrying inactive (null) alleles of genes Wx-A1, Wx-B1, and Wx-D1 with bread wheat cultivars. The molecular markers selected for the study allowed identification of valuable breeding material carrying both single null alleles of Wx genes and their combinations in its genome. A combination of two null alleles (Wx-A1b + Wx-D1b) was detected in 30 lines. The presence of three null alleles (Wx-A1b + Wx-B1b + Wx-D1b), which corresponded to fully Wx wheat, was found in one line. We selected 37 lines that combined the presence of the Wx-B1e allele with the Wx-A1b and Wx-D1b null alleles. The Wx-A1b + Wx-B1e combination was identified in 26 lines, and 24 lines carried the combination of alleles Wx-B1e + Wx-D1b. The mutant forms PI619381, PI619384, and PI619386 were identified as carriers of the functional Wx-B1e allele. The Wx-A1b and Wx-B1e alleles could have been transferred to the studied lines from the donors used or from the Starshina and Korotyshka varieties, respectively. The mutant forms used in the crosses are donors of the Wx-B1b and Wx-D1b alleles. The use of molecular markers chosen by us for identification of the allelic state of the Wx-A1, Wx-B1, and Wx-D1 genes can provide grounds for marker-assisted selection for this trait. Selected lines found to possess null alleles of the Wx genes are applicable in breeding programs aimed at the improvement of technological qualities of grain and raise of bread wheat varieties with modified starch properties.